Ultrafast Microfiber Humidity Sensor Based on Three Dimensional Molybdenum Disulfide Network Cladding - Guo, Pan; Cui, Danting; Dai, Qiaofeng; Cheng, Hongdao; Yu, Jianhui; Guan, Heyuan; Luo, Yunhan; Lu, Huihui; Xiao, Yi; Zhong, Yongchun; Zhu, Wenguo; Chen, Zhe (Frontiers in Physics, 2022)
We demonstrate an ultrafast humidity micro-fiber sensor based on molybdenum disulfide (MoS2) cladding with three dimensional network structure. The high surface-to-volume rations and porous mesh structure improve the interaction of between MoS2 and water molecules, further enhancing the performance of the humidity sensor. The results demonstrated that the sensor can perform in a wide relative humidity (RH) range between 10 %RH to 90 %RH with rapid dynamic behavior (response and recovery time are 0.090 s and 0.130 s respectively). The sum of response and recovery time (total time) is 0.220 s, which is the fastest in the reported MoS2-based humidity sensors. The sensitivity of this sensor is up to -1.501 dB/%RH in the RH range (77 %RH - 90 %RH). Such a high performance RH sensor will have a wide range of application potential in chemical processing, various medical diagnostics and so on.